Evidence for seismicity in the lower crust and upper mantle in the Nepal Himalaya, implication for the rheology of the lithosphere - Rajaure, S; Sapkota, SN; Avouac, JP; Bollinger, L (Journal of Nepal Geological Society, 2008)
It has recently been argued that the strength of the continental lithosphere lies in the crust with the upper mantle being extremely weak. Pivotal to this argument is the observation that most of the seismicity occurs in the crust and that the elastic thickness of continental plates is generally comparable to the depth range of the seismicity. This hypothesis contradicts the earlier view that seismicity is bimodal with earthquakes occurring either in the shallow crust or in the upper mantle, a view that was first promoted based on the seismicity in the Himalaya and Tibet, and on model of the lithosphere rheology derived from experimental rock mechanics. Here we test whether this hypothesis applies in the Nepal Himalaya in view of recent progress on the Moho geometry using the seismicity recorded by the National Seismological Centre of Department of Mines and Geology, Nepal. The seismicity of Nepal Himalaya is characterized by a linear and continuous belt of micro-seismic activity which runs due NW-SE. Majority of the earthquakes have indeed shallow depths and the depth ranges between 10 and 25 km. However a number of earthquakes are relatively deeper (23<depth<70) either beneath the Himalaya or the Terai Plain, this is for example the case of the 1988 Udayapur earthquake mainshock and aftershocks occurred below mantle as has been demonstrated from waveform modeling. To assess further the depth distribution of earthquakes in the Himalaya we have relocated the seismicity recorded at the National Seismological Centre (NSC) seismic stations. The data comes from the bulletins of NSC of Department of Mines and Geology (DMG), Government of Nepal, and were relocated using the double difference technique. Hypocenters are next compared with the location of the Moho derived from seismic experiments which were run across the Himalaya of central Nepal and eastern Tibet. Most earthquakes’ depths fall in the range between 10 and 25 km revealing that the upper part of the crust responding brittally to accumulating stress induced by the ongoing collision between Indian Plate and the Eurasian Plate. Deeper earthquakes (deeper than km 40) with relatively well constrained hypocentral depth, though far less numerous, are also observed. Depth vs RMS plots of such earthquakes give very interesting results and indicate that the earthquakes probably fall either in the upper mantle or lower crust beneath Nepal Himalaya. The depth distribution shows that, in the Terai region, the rare seismic activity is taking place below or around the Moho depth. In the Himalaya where depth to Moho is about 55 km from gravity studies and seismic studies, some earthquakes fall in the upper mantle. A similar conclusion was reached by using the seismicity recorded during the HIMNT experiment. Recently three earthquakes occurred near or below the Moho based on the depths determined from arrival times at the seismic network of Department of Mines and Geology. To reduce the uncertainties either the current geometry of station-distribution should be modified so that the seismicity would lie well inside the network or a couple of temporary seismic stations should augment the currently existing network especially in the far-west. In addition to modification in the geometry of the network, some short period stations must be replaced by either broadband seismic stations or long period seismic stations. Data from such three component stations would help to routinely determine better depths of earthquakes using waveform inversion technique. In any case the data available to date makes it clear that both the upper mantle and lower crust at front of the Himalayan range are deforming brittally, generating earthquakes. This shows that there is no weak decoupling lower crust, as also inferred from gravity modeling assuming the classical ‘jelly-sandwich’ rheology. So it is probable that both the crustal and upper mantle contribute to the strength of the lithosphere needed to support the weight of the Himalayan arc. Journal of Nepal Geological Society, 2007, Vol. 36 (Sp. Issue) p.13